Small Screen Technology Use Among Indigenous Boarding School Adolescents from Remote Regions of Western Australia - Johnson, Genevieve Marie; Oliver, Rhonda (The Australian Journal of Indigenous Education, 2014)
The uptake of small screen technology by adolescents is widespread, particularly in industrial nations. Whether the same is true for Australian Aboriginal youth is less clear as there is a dearth of research in this regard. Therefore, in this exploratory study the use of small screen technology by Indigenous students was examined. Twenty-four Indigenous adolescents (mean age 16.4 years) attending a boarding school in a remote region of Western Australia participated in individual and in-depth structured interviews that queried their use of: (1) television, (2) video games, (3) computers, (4) the internet, and (5) mobile phones. The results showed that mobile phones were the most frequently used and the most popular (i.e., they were nominated as first choice in a hypothetical scenario), followed by the internet, whereas television, video games and computers were used less often. It did appear that mobile phones were used by participating Aboriginal adolescents in ways similar to non-Indigenous adolescents (e.g., not only to make phone calls, but also to send text messages and access the internet). However, their mobile phone use did reflect differences based on their cultural values and identity, and also reflected their physical distance from their family (i.e., because of their enrolment at a boarding school). This study supports anecdotal evidence of a rapid uptake of mobile phones by Indigenous adolescents. It also suggests that as the small screen technology of choice, they have the potential to be utilised for educational opportunities.